DAMPAK TRANSFER FISKAL DAN BELANJA MODAL PEMERINTAH DAERAH TERHADAP PEREKONOMIAN SEKTORAL, KETIMPANGAN DAN KEMISKINAN DI INDONESIA - Nor Qomariyah; Suharno Suharno; Dominicus Savio Priyarsono (IPB University, 2016)
National economic development goal is to improve the welfare of society and to create equitable distribution of income (Todaro and Smith, 2006). In other words, the success of economic development is indicated by the reduction of poverty and income inequality. Poverty is fundamental problem in the economic development of Indonesia and other developing countries in general. The main objectives of this study are to evaluate impacts of Infrastructural budgetary allocation on GDRP sectoral, inequality, and poverty in Indonesian provinces both in the areas where the contribution of the agricultural sector to GDRP is either high or low, in the era of fiscal decentralization. The dynamic simultaneous equation models were used in this study. It used pooled data of 2009-2013 and cross section data of 19 provinces where classified into two groups, based on the contribution of agriculture sector to the respective regional economy. The methode for parameter estimation used in this study was 2SLS. The result of the study showed that the budgetary allocation for infrastructure and agriculture increase the employment and the GRDP sectoral, decrease income inequality, and then reduce poverty both in the areas where the contribution of the agricultural sector to GRDP is either high or low. This study recomended that the central government should improve the injection of funds directly to the regions through a special allocation fund for infrastructure and agriculture as an effective impact on reducing poverty. Keywords: Economic growth, Inequalty, Infrastructure, Poverty, Specific allocation fund